Pengiraan Sel Barah Melalui Nilai Tahap Kalaan Kelabu - Hamim, Mohamad Hidayat (Universiti Sains Malaysia, 2006)
Breast cancer is a leading cause of death among women. Many researches about breast cancer have been done since long time ago to find out any method of treatment, preventing methods and the foundation of infection of breast cancer. This research introduces a method to identify a sign of breast cancer using image processing. Generally, the method used is by taking an image of breast cell using an electron microscope due to breast cell has a small size. An image is taken and will be processed digitally by computer. The analysis process is done by using a grayscale form. An image with a cancer cell gives a different scale value. Then, the scale value will be analyzed using C++ Builder software and represented in a histogram form. C++ Builder software has been chosen because this software is user friendly and has an interesting interface an easy to use. What user needs to do is only put in a digital image as an input to the programming developed and image analysis will be the output for the user.